Estudio de pre-factibilidad para la instalación de una planta procesadora de hojuelas de quinua - Álvarez Cano Fernández, María Alejandra (2016)
The present study of feasibility for the implementation of a sweetened quinoa flakes processing plant, destined to the NSE B and C from Lima, brings the required information to determine the project feasibility